Simple Surgical Method for a Native Arteriovenous Fistula of Chronic Hemodialysis Patients and the Patency Rate. Issue 10 (November 2015) - Tsuchida, Kenji; Nagai, Kojiro; Yokota, Narushi; Okada, Daigo; Muromiya, Yasuhito; Suenaga, Takehiro; Ueda, Yuka; Kawahara, Kana; Kanayama, Hiro-omi; Minakuchi, Jun
Background/Aim: The maintenance and control of vascular access in chronic hemodialysis patients are causing serious problems not only in the quality of life of patients but also in the medical economy. In this regard, we investigated the cumulative patency rate of native arteriovenous fistula (AVF) as a vascular access. Methods: Simple surgical method for a native AVF is selected. The cumulative patency rate of AVF was compared for each parameter. More particularly, the patency rate in the AVF was investigated by primary disease, age at the time of operation, gender, condition, and site. Furthermore, the influence of factors, including primary disease, gender, age at the time of operation (1 year old), and dialysis period (1 year) on the patency rate, was investigated using Cox's proportional hazard model. Results: The patency rate of AVF was 85.6, 75.0, 67.5, 52.2% for 12, 36, 60, 120 months, respectively. When the patency rate was investigated by factor, the rate was significantly higher in the males than females. When the influence of risk factors on the patency rate was investigated, the significant and independent risk factors in all the cases were 'female' sex. Conclusions: The AVF is considered as the vascular access with the highest patency rate in the chronic hemodialysis patients. However, the factor influencing this rate is gender. In conclusion, female has a higher risk than male.